Acral lentiginous melanoma: a skin cancer with unfavourable prognostic features: a study of the German central malignant melanoma registry (CMMR) in 2050 patients - Teramoto, Yukiko; Hassel, Jessica C.; Goerdt, Sergij (British journal of dermatology, 2018)
Background Acral lentiginous melanoma (ALM) is one of the four major subtypes in cutaneous melanoma (CM). Although ALM has a poorer prognosis than other CM subtypes, the prognostic factors associated with ALM have only been verified in small-sized cohorts because of the low incidence of ALM worldwide. Objectives To investigate the clinical characteristics of ALM and to evaluate their prognostic values based on a large dataset from the Central Malignant Melanoma Registry (CMMR) of the German Dermatologic Society. Methods The Kaplan-Meier method was used to estimate the potential influence of clinical and histological parameters on ALM disease-specific survival (DSS) curves, which were compared using the log-rank test. A Cox proportional hazards model was used to identify independent prognostic factors for DSS. Results In total, 2050 patients with ALM were identified from 58 949 patients with CM recorded by the CMMR with follow-up data. In multivariate analyses, age (P = 0·006), ulceration (P = 0·013), tumour thickness (P < 0·001) and tumour spread (P < 0·001) turned out to be significant prognostic factors for DSS in ALM whereas sex, nevus association and level of invasion were not independent factors. Conclusions ALM has the same prognostic factors as other subtypes of melanoma. Unfavourable prognosis probably derives from the delay in diagnosis in comparison with other melanoma subtypes.